2013
DOI: 10.1063/1.4789903
|View full text |Cite
|
Sign up to set email alerts
|

An in situ diffraction study of domain wall motion contributions to the frequency dispersion of the piezoelectric coefficient in lead zirconate titanate

Abstract: Two dimensional ferroelectric domain patterns in Yb3+ optically active LiNbO3 fabricated by direct electron beam writing Appl. Phys. Lett. 102, 042910 (2013) Local probing of the interaction between intrinsic defects and ferroelectric domain walls in lithium niobate Appl. Phys. Lett. 102, 042905 (2013) Structural investigation of interface and defects in epitaxial Bi3.25La0.75Ti3O12 film on SrRuO3/SrTiO3 (111) and (100) J. Appl. Phys. 113, 044102 (2013) Piezo-strain induced non-volatile resistance sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 21 publications
1
17
1
1
Order By: Relevance
“…It is widely accepted that domain wall motions can contribute to functional responses in ferroelectrics and there has been some experimental evidence for these extrinsic effects revealed by neutron diffraction and high-frequency dielectric measurements [165167]. Considering the domain wall motion is a relaxation process, frequency related loss behavior could provide some quantified measurements for the relaxation coefficient, so that high frequency ultrasonic spectroscopy should be a powerful tool to evaluate the extrinsic loss in ferroelectrics.…”
Section: Extrinsic Loss Mechanismsmentioning
confidence: 99%
“…It is widely accepted that domain wall motions can contribute to functional responses in ferroelectrics and there has been some experimental evidence for these extrinsic effects revealed by neutron diffraction and high-frequency dielectric measurements [165167]. Considering the domain wall motion is a relaxation process, frequency related loss behavior could provide some quantified measurements for the relaxation coefficient, so that high frequency ultrasonic spectroscopy should be a powerful tool to evaluate the extrinsic loss in ferroelectrics.…”
Section: Extrinsic Loss Mechanismsmentioning
confidence: 99%
“…In particular, domain rearrangement and lattice strain in large-domain electroceramic materials have been analysed under various field conditions1011, but such analyses give no insight into atomic displacements. Diffraction and imaging techniques available in a transmission electron microscope (TEM) enable single-crystal studies of field-induced phase transitions, lattice distortions, and domain rearrangement in polycrystalline materials1213; however, obtaining quantitative information on atomic displacements from TEM data is difficult.…”
mentioning
confidence: 99%
“…Two examples are polycrystalline piezoelectric materials, whose net piezoelectric effect measured at the macroscale is typically reduced due to the different contributions from randomly oriented nano-to microscopic grains, 4 and ferroelectrics, where nanoscale domains of variously orientated polarisation affect the dielectric susceptibility 5 and piezoelectric response. 6,7 In this context, the advent of atomic force microscopy (AFM) techniques and their ability to probe matter with nanometric lateral resolution has allowed the physical limits of electromechanical phenomena to be explored. [8][9][10][11][12] AFM has been instrumental in ushering in the age of nanotechnology owing to its high resolution and sensitivity across a range of interaction forces, allowing AFM to find applications in materials science, physics, chemistry, and biology.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of domains in ferroelectric samples has been demonstrated to affect macroscopic properties such as the dielectric susceptibility 5 and piezoelectric response. 6,7 Therefore, understanding and controlling domain structures is key to tailoring and optimising the electronic properties of ferroelectric materials. Recently, Lichtensteiger et al have demonstrated using PFM that the insertion of a dielectric spacer layer between a ferroelectric thin film and the bottom electrode led to an increase of the depolarizing field, allowing a polydomain configuration to be tailored in samples presenting a uniform polarisation.…”
Section: Introductionmentioning
confidence: 99%